Case Report: Petrous Apicitis and Otogenic Thrombosis of the Cavernous Sinus in a 10-Year-Old Boy - Bergsma, Patrick; Kunz, Seraina; Kienle, Anna-Lena; Brand, Yves (Frontiers in Surgery, 2021)
Background Petrous apicitis and cavernous sinus thrombosis are exceedingly rare complications of acute otitis media with only few reported cases in the post-antibiotic era. Especially in children, the appropriate management is a subject of controversy. Case Presentation We report the case of a 10-year-old boy who presented to the emergency department with left-sided otalgia, otorrhea, and hearing loss, accompanied by somnolence and high spiking fevers. CT and MRI revealed partially obstructed mastoid air cells including a pneumatized petrous apex. Furthermore, thrombosis of the cavernous sinus and vasculitis of the internal carotid artery on the left side were present. The patient was treated with antibiotics for 6 weeks and anticoagulant therapy for 3 months. Follow-up carried out 3 months post-admission showed complete recanalization of the cavernous sinus on MRI and no otological or neurological symptoms. Conclusion A complicated otitis media with petrous apicitis and cavernous sinus thrombosis in a child can in some cases be managed without surgical intervention.